IMPLEMENTASI PEMBERIAN REWARD KEPADA SISWA KELAS IV SDK WAIARA - Hero, Hermus; Esthakia, Maria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2020)
Education is an effort to foster and develop the human person both from the spiritual and physical aspects as well as gradually. In the learning process it is necessary to motivate students so that they can improve learning outcomes. One of the types of motivation is by giving reward. The purpose of this study was to analyze the understanding of teachers and the implementation of presenting awards to SDK Waiara students. The method used is descriptive qualitative by referring to the qualitative analysis of the data according to Miles and Huberman. The results showed the understanding of the SDK Waira teacher's understanding of the concept of giving. However, some respondents who were interviewed provided information that they had given rewards in class. An award that impacts students' attention in learning.